Liquid single-electrode triboelectric nanogenerator based on graphene oxide dispersion for wearable electronics. (October 2019) - Wu, Yinghong; Luo, Yang; Qu, Jingkui; Daoud, Walid A.; Qi, Tao
Abstract: Owing to the limited deformability and restricted scalability of traditional triboelectric nanogenerator (TENG), liquid single-electrode TENG based on graphene oxide dispersion (GO LS-TENG) was developed in this study. The device exhibits high short-circuit current density of 18.61 mA m −2 at contact frequency of 3 Hz, being much higher than that of reported LS-TENG based on NaCl solution (1.8 mA m −2, 2.3 Hz) and liquid metal (8.6 mA m −2, 3 Hz). Moreover, its maximum power density can reach 4.97 W m −2 (1.99 mW, 3 Hz), which is higher than that of a reported single-electrode TENG based on GO solid electrode (3.13 W m −2, 5 Hz). On palm tapping the device, 87 green LEDs connected in series can be lit up. Robustness, durability and reproducibility tests show high stability, sensitivity, and potential use of this device in wearable electronics. This work demonstrates a novel approach to fabricate LS-TENG with simple structure, high output and high sensitivity for use in highly flexible and deformable wearable devices. Graphical abstract: Image 1 Highlights: Novel liquid single-electrode TENG based on GO dispersion is presented. The maximum power density (power) of GO LS-TENG reaches 4.97 W m −2 (1.99 mW). 87 green LEDs are lit up by palm tapping the device with electrode size of 4 cm 2 . Minute body movement inputs demonstrate great potential in wearable electronics.